Birdwings Butterfly Preservation as a Sustainable Tourism Destination in Menyambouw Manokwari - I Dewa Gde Satrya; Chelsia Renata Tri Wascita (Yayasan Sinergi Widya Nusantara, 2022)
Purpose: This study examines and analyzes the potential development of bird wing butterfly breeding based on community involvement factors, surrounding destinations, and the strategies provided. Research methods: The method used is descriptive qualitative, data mining with interview and direct observation techniques. Findings: The breeding of the bird-wing butterfly (Ornitophera Paradisea) is an effort to conserve rare animals that are only found in eastern Indonesia, especially in the Arfak Mountains. The location of bird's wing butterfly breeding is in the District of Menyambouw, Manokwari, West Papua. Birdwing butterfly breeding initially became a tourist attraction by one of the private sectors. However, due to several factors, the preservation and the villa could not survive and the owner decided to close the operation by delegating the preservation to the local community as managers with an ecotourism approach. Implication: It is important to formulate a strategy for developing birdwing butterfly breeding destinations through partnerships for investment and the establishment of networks between tourist destinations.